Successful Treatment of Caesarean Scar Pregnancies by Local Treatment Only - Shinji Tanigaki; Chie Nagata; Kazunori Ueno; Nobuaki Ozawa; Shinichi Nagaoka; Kei Tanaka; Haruhiko Sago; Mitsutoshi Iwashita (Obstetrics and Gynecology International)
Background. Caesarean scar pregnancy (CSP) is a rare ectopic pregnancy associated with life-threatening complications. To date, no therapeutic protocols have been established. Sono-guided local methotrexate (MTX) injection is a relatively easy and low-invasive treatment. Additional systemic MTX is sometimes needed for CSP cases, especially when β-subunit human chorionic gonadotropin (β-hCG) levels are >20,000 mIU/ml at diagnosis. We report on six cases of CSP treated with local MTX injection, five of which received combined local treatment. Methods. Under intravenous anesthesia, six CSPs including a case with β-hCG levels >20,000 mIU/ml received MTX injection to the gestational sac. Five cases received gestational sac aspiration. Three cases had additional local potassium chloride injection and one case had a saline injection aiming at the fetal heart beat concurrent with MTX injection. MTX was administered weekly if β-hCG levels stayed beyond the expected values. Outcomes. All cases achieved β-hCG normalization without additional systemic MTX, with one case having a successful pregnancy after treatment. Conclusion. Sono-guided local MTX injection with concurrent local treatment might be a potentially effective approach for CSP cases. The accumulation of further cases is necessary to confirm this.